Perancangan dan Pembuatan Pembelajaran Daring (E-Learning) Pada Sekolah Menengah Pertama 1 Tarik Sidoarjo - Mufid, Mohammad Robihul; Marcell Bintang Setiawan; Arif Basofi; Saniyatul Mawaddah; Yunia Ikawati; Arna Fariza; Rosiyah Faradisa; Darmawan Aditama; Fardani Annisa Damastuti (Politeknik Negeri Jember, 2023)
SMP Negeri 1 Tarik is an educational institution located on Jl. Raya Tarik, Tarik, Sidoarjo. In the learning process at SMP Negeri 1 Tarik, so far students have studied face-to-face, and have never used or had a platform that can start learning online. The 2020 pandemic had such an impact on schools that schools had to try to carry out online education, but due to limited platforms for starting online learning it was a challenge in itself.Therefore this research exists to help schools so that if the same situation occurs again, the school will have no trouble, and with this research it helps schools to take advantage of technology, especially the web, in the learning process. This research resulted in an e-learning web-based application or Learning Management System (LMS) which will be useful for students and teachers in the learning process starting from making assignments, managing materials, recording attendance, and giving grades to assignments. Data collection was carried out by means of observation and interviews. From this study, the results of testing with several indicators with scores of Learnability (4.56), Memorability (4.37), Efficiency (4.36), Accuracy (4.47), Satisfaction (4.45). With an average score of (4.44). It can be concluded that the e-learning website for SMP Negeri 1 Tarik can be stated to be easy to learn, effective, and comfortable to use.